Information Technology Regulation and its Impact on Da'wah Media on Tiktok - Marya Ulfa; Sinta Purnamasari; Nikmah Hadiati Salisah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
The development of information technology has brought very significant changes in various aspects of life, including da'wah media. Regulation of information technology is an important factor in determining the direction of da'wah media development, both in terms of freedom of expression, dissemination of information, and protection of content that is considered sensitive. This study discusses how information technology regulations and their impact on da'wah media, including the opportunities and challenges that arise for da'wah preachers when utilizing digital technology. The research method used in this study is a qualitative method with a descriptive approach that aims to describe information technology regulations and their impact on TikTok da'wah media. Data collection techniques used in this study are observation and documentation. The results of the study show that regulations can play an important role as a tool to maintain the ethics and quality of da'wah in the digital space, but on the other hand, regulations can also be an obstacle if they are too restrictive of freedom of expression. Therefore, a balance is needed in regulations so that information technology can be utilized optimally for the advancement of da'wah media.